2017
DOI: 10.1007/s40620-017-0385-y
|View full text |Cite
|
Sign up to set email alerts
|

De novo cancer in patients on dialysis and after renal transplantation: north-western Italy, 1997–2012

Abstract: Our study confirms the increased risk of cancer after transplantation and during dialysis, but showed that virus-related cancers only occur after post-transplant immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 16 publications
3
17
0
1
Order By: Relevance
“…The increased risk of cancer in dialysis patients has been well documented in Asia [3, 6], United States [7], Australia/New Zealand [2], and northern Europe [9]. Conversely, less evidence has been accumulated in southern European countries, such as Italy, where end-stage kidney disease (ESKD) patients represent about 0.1% of the general population [10], and only a small study has been published in the international literature [11].…”
Section: Introductionmentioning
confidence: 99%
“…The increased risk of cancer in dialysis patients has been well documented in Asia [3, 6], United States [7], Australia/New Zealand [2], and northern Europe [9]. Conversely, less evidence has been accumulated in southern European countries, such as Italy, where end-stage kidney disease (ESKD) patients represent about 0.1% of the general population [10], and only a small study has been published in the international literature [11].…”
Section: Introductionmentioning
confidence: 99%
“…When analysing the 21 stcentury literature in relation to the incidence of tumour recurrence after LT, the lack of attention paid to the impact of IS on the outcome of liver cancer recipients is surprising. The link between IS and oncogenesis has been unequivocally proven both in laboratory and clinical settings (24)(25)(26)(27)(28)(29)(30). The increase in cancer risk has already been ascertained in patients receiving IS as well as in patients with an end-stage organ failure.…”
Section: Immunosuppression (Is) and Carcinogenesismentioning
confidence: 99%
“…Nevertheless, only virus-related cancers have a higher incidence after post-transplant IS. Oncogenic viruses can immortalise infected cells by disrupting the cell-cycle control and, in a setting of induced lowered immune surveillance, this phenomenon is likely to cause tumorigenesis (29,30). Basic research is important for further progress in transplantation oncology as demonstrated by the following two examples.…”
Section: Immunosuppression (Is) and Carcinogenesismentioning
confidence: 99%
“…Several inflammatory and oxidative stress mechanisms have been implicated in linking cancer with CKD [18, 19]. End-stage renal disease patients on dialysis or after transplantation are high-risk groups identified for cancer development due to uremia and immunodeficiency [2023]. But, research on cancer and its impact on mortality and renal outcome is scarce in a Caucasian population with advanced CKD (CKD-3-5, not on dialysis) and the question of whether the presence of cancer accelerates the rate of progression of CKD is unexplored, which this study aims to address.…”
Section: Introductionmentioning
confidence: 99%